Clinical and Radiographic Outcomes of Traumatized Immature Permanent Necrotic Teeth after Revascularization/Revitalization Therapy - L. Gibbs, Jennifer; Mohamed A. Saoud, Tarek; Zaazou, Ashraf; Nabil, Ahmed; Moussa, Sybel; M. Lin, Louis (Libyan Journal of Dentistry, 2017)
Introduction: Revascularization treatment is rapidly becoming an accepted treatment alternative for the management of endodontic pathology in immature permanent teeth with necrotic dental pulps. However, the success and timing of clinical resolution of symptoms, and radiographic outcomes of interest, such as continued hard tissue deposition within the root, are largely unknown. Methods: In this prospective cohort study, 20 teeth were treated with a standardized revascularization treatment protocol and monitored for clinical and radiographic changes for 1 year. Standardized radiographs were collected at regular intervals, and radiographic changes were quantified. Results: All 20 treated teeth survived during the 12- month follow-up period, and all 20 also met the clinical criteria for success at 12 months. As a group, the treated teeth showed a statistically significant increase in radio- graphic root width and length and a decrease in apical diameter, although the changes in many cases were quite small (such that the clinical significance is unclear). The within-case percent change in apical diameter after 3 months was 16% and had increased to 79% by 12 months, with 55% (11/20) showing complete apical closure. The within-case percent change in root length averaged less than 1% at 3 months and increased to 5% at 12 months. The within-case percent change in root thickness averaged 3% at 3 months and 21% at 12 months. Conclusions: Although clinical success was highly predictable with this procedure, clinically meaningful radiographic root thickening and length- ening are less predictable after 1-year of follow-up. Api- cal closure is the most consistentradiographic finding.(J Endod 2014;40:1946–1952).